Does it get better? LGBTQ social work students and experiences with harmful discourse. Issue 2 (3rd April 2019) - Atteberry-Ash, Brittanie; Speer, Stephanie Rachel; K. Kattari, Shanna; Kinney, M. Killian
Abstract: Although the field of social work is grounded in social justice, the social work educational experience, including classrooms, may not live up to this value, especially for lesbian, gay, bisexual, transgender, and queer (LGBTQ) students. Using a qualitative phenomenological approach, this study examined the experiences of harmful discourse in social work classrooms for LGBTQ students. Findings indicate that students experienced being misgendered, tokenized, and erased through cis-/heteronormative language and classroom teachings. Although social work is guided by frameworks of social justice, microaggressions and discrimination may be vaguely glossed over, if addressed at all. This study highlights the gap between the values social work teaches and how social work education is delivered.